GANDRUNG EXISTENCE REALITY IN BANYUWANGI OSING COMMUNITIES - Darwis Faisal Maulana; Imam Suyitno (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2020)
Gandrung is a distinctive art that has become the mascot of Banyuwangi tourism. Behind the fame of Gandrung's art today, there is a debate concerning the existence of Gandrung. The debate occurred between two groups who had different views about Gandrung. This study aims to dissect the reality of the existence of Gandrung based on these different views. The focus of this research is the reality of Gandrung in the Osing community in Banyuwangi. This research uses a qualitative approach. The data of this research are in the form of utterances sourced from the results of interviews with Gandrung art activist informants. Based on data analysis, it was found that Gandrung's reality in Banyuwangi included: (1) Gandrung and art for struggle, (2) Gandrung differences then and now, (3) Gandrung art is not a ritual, (4) Gandrung dancers are not highly educated, (5) Gandrung is considered far from religion, and (6) Gandrung is a good user of witchcraft.